2008
DOI: 10.1088/0957-4484/19/30/305604
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of few-layer graphene via microwave plasma-enhanced chemical vapour deposition

Abstract: If graphene is ever going to live up to the promises of future nanoelectronic devices, an easy and cheap route for mass production is an essential requirement. A way to extend the capabilities of plasma-enhanced chemical vapour deposition to the synthesis of freestanding few-layer graphene is presented. Micrometre-wide flakes consisting of four to six atomic layers of stacked graphene sheets have been synthesized by controlled recombination of carbon radicals in a microwave plasma. A simple and highly reproduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

19
296
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 487 publications
(316 citation statements)
references
References 24 publications
19
296
0
1
Order By: Relevance
“…There have been some reports of plasma-based methods to decrease the process temperature including the use of microwave plasma CVD to synthesize graphene on nickel foil, 7 surface wave plasma CVD to synthesize graphene at low temperatures in the range of 300 • C to 400 • C on large area conductive electrodes 8,9 and the plasma-assisted deposition of graphene on copper foils at temperatures down to 600 • C. [10][11][12] Although these works show that PECVD is a promising method for the synthesis of graphene, the resulting carbon structures often lack of quality being FLG with considerable amount of defects. 11,12 The high defect density in PECVD graphene is referred to energetic particles from the plasma interacting with the growing surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some reports of plasma-based methods to decrease the process temperature including the use of microwave plasma CVD to synthesize graphene on nickel foil, 7 surface wave plasma CVD to synthesize graphene at low temperatures in the range of 300 • C to 400 • C on large area conductive electrodes 8,9 and the plasma-assisted deposition of graphene on copper foils at temperatures down to 600 • C. [10][11][12] Although these works show that PECVD is a promising method for the synthesis of graphene, the resulting carbon structures often lack of quality being FLG with considerable amount of defects. 11,12 The high defect density in PECVD graphene is referred to energetic particles from the plasma interacting with the growing surface.…”
Section: Introductionmentioning
confidence: 99%
“…11,12 The high defect density in PECVD graphene is referred to energetic particles from the plasma interacting with the growing surface. Nevertheless there have been experiments proving that SLG of good quality can be deposited by plasma-assisted methods.…”
Section: Introductionmentioning
confidence: 99%
“…12 Chemical vapor deposition (CVD) method of synthesizing few layer graphene (FLG) was first discovered in 2006 13 , and to date, mature millimeter-sized monolayer graphene sheets can be achieved and transferred to many substrates by plasma-enhanced CVD process. 14 But direct growth of large-sized graphene and on different substrates still need to be explored and industrial-scale synthesis is to be solved. Chemical reduction of graphene oxide (rGO) was thought to be a promising approach, as graphene oxide (GO) can be easily exfoliated through sonication in liquid phase, 15,16 and chemical reduction process can decrease the functional defects produced by oxidation.…”
mentioning
confidence: 99%
“…It is also found that G band is broadened and shifted to 1572 cm -1 [60]. In addition, the D band is observed at 1336 cm -1 becomes prominent, is indicating the reduction in size of the plane sp 2 domains, possibly due to the extensive oxidation [14]. Similarly, we observe the major peaks of G and D bands for the graphene at 1336 cm -1 and 1572 cm -1 indicating the high purity of carbon compound existing in singular layers stacking.…”
Section: Raman Spectroscopymentioning
confidence: 99%